Computed Tomographic Analysis of Mandibular Tori and Their Relationship to Remaining Teeth - Kai Shibaguchi; Kenzo Morinaga; Yuki Magori; Toyohiro Kagawa; Takashi Matsuura (Diagnostics, 2025)
Objectives: Mandibular tori (bilateral, asymptomatic, lingual mandibular protuberances) often remain untreated. When considering surgical resection, understanding the shape, size, and position of the tori at the bone level is crucial. However, collecting accurate information regarding these characteristics is challenging in cases where the oral mucosa is prominent on the floor of the mouth. Methods: We conducted retrospective surveys at Fukuoka Dental College Medical and Dental General Hospital using computed tomographic (CT) image analysis software (Simplant Pro 18.0). The specific aims of this study were to evaluate the appearance rate of mandibular tori by morphological type, size, location, and CT values and their relationship with the remaining teeth in 1176 patients. These patients underwent simple mandibular CT tomography. We used t-tests to analyze the data. Results: Approximately 10% of the identified tori were pedunculated and difficult to diagnose through visual inspection alone. In all the age groups > 30 years, patients with mandibular tori had a lower rate of tooth loss and a higher rate of remaining occlusal support than healthy subjects. The mean CT value of the mandibular tori was >1350 Hounsfield units (HU). Conclusions: These findings provide insights into future classification and treatment planning for mandibular tori, including that in regard to mandibular ridge resection and factors that may contribute to mandibular torus development or progression, and validate the use of excised bone tissue as a bone graft material.